Generative AI's environmental footprint poses difficult tradeoffs for agrifood systems in low- and middle-income countries - Margolies, Amy (International Food Policy Research Institute, 2025)
The generative artificial intelligence (gen AI) revolution is not just digital - it is also physical. Data center complexes are expanding globally to meet rapidly increasing computing and data storage demands of generative AI (Figure 1). The extent of AI's immense energy requirements is still largely unknown, but estimates indicate that by 2026, data centers could consume over 1,000 terawatt-hours (TWh) of electricity - more than doubling since 2022 and equivalent to Japan's total power usage.